5n-6(n+2)=14

Simple and best practice solution for 5n-6(n+2)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-6(n+2)=14 equation:


Simplifying
5n + -6(n + 2) = 14

Reorder the terms:
5n + -6(2 + n) = 14
5n + (2 * -6 + n * -6) = 14
5n + (-12 + -6n) = 14

Reorder the terms:
-12 + 5n + -6n = 14

Combine like terms: 5n + -6n = -1n
-12 + -1n = 14

Solving
-12 + -1n = 14

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -1n = 14 + 12

Combine like terms: -12 + 12 = 0
0 + -1n = 14 + 12
-1n = 14 + 12

Combine like terms: 14 + 12 = 26
-1n = 26

Divide each side by '-1'.
n = -26

Simplifying
n = -26

See similar equations:

| -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 | | 61=16+5(x-3) | | 4.2q-5.9-5.5q=-2.3q-3.6 | | 8p=2(p+9) | | 8(w-2)= | | 100.39=28.90+49.99+2x | | (2x+5)+(x-2)= | | a+(a+450000)=625000000 | | 38.5=2x-1.5+2x-1.5+x+x+x+7.2 | | 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o | | x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= | | 66.8=2x+4.7 | | 5p-(4p-4)=17 | | 19.8=x+2.9+4.5+x | | 9.9x+38.57=-10.1+38.41 | | 15(x+1)=5(4x) | | y=zr | | p=0.4+-350.002x | | 2w^9-20w^8-48w^7= |

Equations solver categories